Strongly exposed points in the unit ball of trace-class operators - Kourosh Nourouzi (International Journal of Mathematics and Mathematical Sciences)
A theorem of Arazy shows that every extreme point of the unit ball of trace-class operators is strongly exposed. We give this result a simpler and direct proof here.